Association Between Wine Consumption and Cognitive Decline in Older People: A Systematic Review and Meta-Analysis of Longitudinal Studies - Lucerón-Lucas-Torres, Maribel; Cavero-Redondo, Iván; Martínez-Vizcaíno, Vicente; Saz-Lara, Alicia; Pascual-Morena, Carlos; Álvarez-Bueno, Celia (Frontiers in Nutrition, 2022)
Background Low-to-moderate alcohol consumption appears to have potential health benefits. Existing evidence concludes that wine may be associated with a lower incidence of certain diseases. This systematic review and meta-analysis aim to examine evidence on the association between wine consumption and cognitive decline and to analyze whether this association varies depending on the wine consumption level or is affected by individual and study characteristics, including mean age, percentage of women participants, and follow-up time. Methods In this systematic review and meta-analysis, we undertook a search in MEDLINE (via PubMed), Scopus, Cochrane, and Web of Science databases for longitudinal studies measuring the association between wine consumption and cognitive decline from their inception to May 2021. Effect sizes were calculated using the DerSimonian and Laird and Hartung-Knapp-Sidik-Jonkman methods. Results The search retrieved 6,055 articles, 16 of which were included in this systematic review. In total, 12 studies were included in the meta-analysis. The studies were published between 1997 and 2019. They were conducted in nine different countries. The sample size of the included studies ranged from 360 to 10,308 with a mean age of 70 years old. Using the DerSimoniand and Laird method, the pooled RR for the effect of wine consumption on cognitive decline was 0.72 (95% CI 0.63–0.80; I2 = 82.4%; τ2: 0.0154). Using the Hartung-Knapp-Sidik-Jonkman method, the RR was 0.65 (95% CI 0.52–0.79; I2 = 94,531%; τ2: 0.057). Conclusions This study may show a protective effect of wine consumption against cognitive decline. However, it would be important for future research to differentiate the types of wine within consumption.